Intraplate Seamounts as a Window into Deep Earth Processes - Koppers, A; Watts, A (2010)
Seamounts are windows into the deep Earth that are helping to elucidate various deep Earth processes. For example, thermal and mechanical properties of oceanic lithosphere can be determined from the flexing of oceanic crust caused by the growth of seamounts on top of it. Seamount trails also are excellent recorders of absolute plate tectonic motions and provide key insights into the relationships among plate motion, plume motion, whole-Earth motion, and mantle convection. And, because seamounts are created from the partial melts of deep mantle sources, they offer unique glimpses into the chemical development and heterogeneity of Earth's deepest regions. Current research efforts focus on resolving the fundamental differences between magmas generated by passive upwelling from upper mantle regions and deep mantle plumes rising from the core-mantle boundary, mapping the different modes of mantle plumes and mantle convection, reconciling fixed and nonfixed mantle plumes, and understanding the prolonged volcanic evolution of seamounts. The role of intraplate seamounts is pivotal to this research, and we must collect vast amounts more geochemical and geophysical data to advance our knowledge. These data needs leave the ocean wide open for future seamount exploration.